2004
DOI: 10.1002/oti.198
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity movement pattern of a common drinking task in well elderly women: a pilot study

Abstract: Retraining of the upper limb during neurological rehabilitation often involves preparatory therapeutic exercises of concentric and eccentric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(34 reference statements)
0
15
1
Order By: Relevance
“…This consisted of small sense coils (diameter ~ 2 cm) that are attached to the moving limbs to record angular movements within an electromagnetic field created by field coils (diameter ~180 cm). Studies using similar systems have been reported in the literature (Andree and Maitra, 2002;Maitra and Junkins, 2004). In our study, one sense coil was attached to the upper arm (over the radial side of the biceps) to record upper arm movements in the sagital plane during reaching.…”
Section: Methodsmentioning
confidence: 94%
“…This consisted of small sense coils (diameter ~ 2 cm) that are attached to the moving limbs to record angular movements within an electromagnetic field created by field coils (diameter ~180 cm). Studies using similar systems have been reported in the literature (Andree and Maitra, 2002;Maitra and Junkins, 2004). In our study, one sense coil was attached to the upper arm (over the radial side of the biceps) to record upper arm movements in the sagital plane during reaching.…”
Section: Methodsmentioning
confidence: 94%
“…These results were consistent with previous studies that have shown maturation of upper limb movements in children aged from 3 to 18 years 10,24 and significant aging in the elderly. 4,20 Indeed, older children's movements (>8 years) were larger, 10,24 smoother, and more linear, accurate and reproducible 10 than younger children's movements (<8 years). Moreover, the movements of elderly individuals (age mean ± SD in years: [75.3 ± 4.0]) were slower and less smooth than the movements of young adults (age mean ± SD in years: 20 Surprisingly, the speed index for both geometrical tasks decreased throughout life.…”
Section: Age Effects and Normative Values For Upper Limb Kinematicsmentioning
confidence: 95%
“…4,20 Indeed, older children's movements (>8 years) were larger, 10,24 smoother, and more linear, accurate and reproducible 10 than younger children's movements (<8 years). Moreover, the movements of elderly individuals (age mean ± SD in years: [75.3 ± 4.0]) were slower and less smooth than the movements of young adults (age mean ± SD in years: 20 Surprisingly, the speed index for both geometrical tasks decreased throughout life. The speed of the upper limb movements may have been influenced by the ''spontaneous speeds'' instruction.…”
Section: Age Effects and Normative Values For Upper Limb Kinematicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although motion analysis is complex, it has been reported to be effective in evaluating the characteristics of the upper extremity function of various movement disorders since it has the advantage of being able to provide the kinematic data for each joint [15,16]. When looking into previous studies that examine the quantitative and qualitative movements of the upper extremity through the use of kinematic motion analysis, many of them involved healthy subjects performing task-oriented reaching exercises in order to understand the mechanisms and biomechanical properties of motor control [17][18][19].…”
Section: Original Articlementioning
confidence: 99%